Helena Kapełuś and Her Intense Folklore Studies - Grochowski, Piotr (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
Review: Helena Kapełuś, Wszystko jest folklorystyką. Wybrane prace, redakcja Regina Gromacka, wstęp Magdalena Kapełuś, Wydawnictwo Agade, Warszawa 2022.